Performance of a value stock portfolio - Louženský, Filip (2020)
The purpose of this thesis is to explain the basic principles of value investing and to discover a relationship between fundamental financial ratios and capital return. This study uses multiple sources to determine, whether a portfolio of selected value shares may outperform any main benchmark (DJIA, S&P 500) in the long run. Discussed literature proves the assumption of value portfolio having better results than the market itself to some extent. For this research, I have used data from the US stock market.